Systematics of New World Maytenus (Celastraceae) and a New Delimitation of the Genus - Biral, Leonardo [UNESP]; Simmons, Mark P.; Smidt, Eric C.; Tembrock, Luke R.; Bolson, Monica [UNESP]; Archer, Robert H.; Lombardi, Julio A. [UNESP] (Amer Soc Plant Taxonomists, 2017)
Maytenus species are distributed in the New World from Argentina to the U. S. A. The genus delimitation has been controversial, especially in relation to the inclusion of Gymnosporia. Maytenus has been treated in a broad sense such that it was considered widely distributed in tropics and subtropics worldwide. Even in its current restricted circumscription, the genus remains paraphyletic with Fraunhofera and Plenckia nested within it. We increased taxon sampling relative to previous studies and sampled species representing the greatest morphological diversity from throughout the geographic distribution in order to confidently delimit monophyletic genera. The phylogenywas inferred using nuclear (ITS and 26S rDNA) and plastid (matK and trnL-F) gene regions together with morphological characters. The species currently recognized as Maytenus were resolved in three distinct clades. Delimitation of a single large genus, by including Fraunhofera and Plenckia within Maytenus, would result in a morphologically heterogeneous group. Instead we segregated Maytenus into two genera, re-established Tricerma, and maintain Fraunhofera and Plenckia as distinct genera. All of these genera are morphologically distinct from each other, primarily based on fruit characters. A total of 123 new combinations under the generic name Monteverdia are provided for species in the clade that does not contain the type of Maytenus.
Keywords: Celastroideae; Fraunhofera; Monteverdia; Plenckia; Tricerma; Viposia